Divide and Choose as Dual Participatory Justice: A Comparative Framework for UAE Civil Disputes - Chami, Yassine; Dran , Driss ed (Faculty of Law, University of Muhammadiyah Malang, 2026)
This study introduces a novel conceptual model,